(3HQfGeL JOQjHi dJfejI egGQI EOGQI GdhbJ deYdeGJ QjGV GdCWaGd (B/ s - (3SeQ eMehO Thbi YHOGdTGai ESeGYjds; (3GHJgGL eMehO oWdHg (B: s; (3TjeGA eMeO Ydi TfOi (B: s ((3GdbGgQI (B: s (3SeQ eMehO Thbi YHOGdTGai ESeGYjd (B: s, 2021)
(3gOaJ GdOQGSI GdMGdjI Edi JUeje HQfGeL JOQjHi dJfejI egGQI EOGQI GdhbJ deYdeGJ QjGV GdCWaGd(B: (3h GSJNOeJ GdHGMKI GdefgL GdJLQjHi Ph GdeLehYJjf (B((3GdeLehYI GdJLQjHjI (B- (3GdeLehYI GdVGHWI(B) (3defGSHJg dWHjYI GdOQGSI(B. (3h JchfJ YjfI GdHMK ef (B(60) (3eYdeI ef eYdeGJ QjGV GdCWaGd(B: (3JQGhMJ CYeGQgf GdRefjI eG Hjf (B(24- 40) (3YGeG h Je GNJjGQgf HWQjbI YThGFjI(B: (3h Je JbSjegf Edi eLehYJjf (B(30) (3eYdeI ddeLehYI GdJLQjHjI(B: (30) (3eYdeI ddeLehYI GdVGHWI(B: (3h GSJNOeJ GdHGMKI GdCOhGJ GdJGdjI(B: (3ESJeGQI ESJWdGY QCi eYdeGJ QjGV GdCWaGd (B((3EYOGO GdHGMKI(B): (3HWGbI edGMXI egGQI EOGQI GdhbJ deYdeGJ QjGV GdCWaGd (B((3EYOGO GdHGMKI(B): (3GdENJHGQ GdJMUjdi ai egGQI EOGQI GdhbJ deYdeGJ QjGV GdCWaGd (B((3EYOGO GdHGMKI(B): (3GdHQfGeL GdJOQjHi (B((3EYOGO(B: (3GdHGMKI(B). (3h JhUdJ GdOQGSI ddfJGFL GdJGdjI(B: (3Cf GdHQfGeL GdJOQjHi GdeSJNOe COi Edj JMSf edMhX ai JfejI egGQI EOGQI GdhbJ deYdeGJ QjGV GdCWaGd(B: (3h Cf GdHQfGeL GdeSJNOe ai GdOQGSI dg JCKjQ ai WQjbI COGA GdeYdeI ddegGe GdeWdhHg efgG(B: (3h GSJeQ CKQ GdHQfGeL Edi GdbjGS GdJJHYi eeG jOd Ydi fLGM GdHQfGeL h aGYdjJgs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdJQHhjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3EOGQIs; (3GdeOQShfs; (3GdhbJs; (3EOGQI GdhbJs; (3GdHQfGeL GdJOQjHis; (3eYdeGJ QjGV GdCWaGds